Intraoperative care of severe bronchospasm - J. Du; J. D. Tobias (Pediatric Anesthesia and Critical Care Journal, 2021)
The incidence of asthma, a chronic inflammatory disease of the airway that increases the risk of intraoperative bronchospasm, is increasing and thus a higher number of asthmatic patients are presenting for anesthetic care. As intraoperative bronchospasm can be an acute life-threat- ening event, recognizing and mitigating risk factors as well as having a specific treatment algorithm in place may be helpful to facilitate safe care. We present a 3- year-old child who developed intraoperative bron- chospasm. The differential diagnosis of intraoperative wheezing is presented, risk factors for intraoperative bronchospasm reviewed, and a treatment algorithm pro- posed.